2022
DOI: 10.32604/biocell.2022.017248
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells: As a multi-target cell therapy for clearing β-amyloid deposition in Alzheimer’s disease

Abstract: Extracellular β-amyloid (Aβ) plaques and neurofibrillary tangles (NFTs) are the pathological hallmarks of Alzheimer's disease (AD). Studies have shown that aggregates of extracellular Aβ can induce neuroinflammation mediated neurotoxic signaling through microglial activation and release of pro-inflammatory factors. Thus, modulation of Aβ might be a potential therapeutic strategy for modifying disease progression. Recently, a large number of reports have confirmed the beneficial effects of mesenchymal stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…It has been suggested that the prolonged presence of microglial reaction after TBI increases the chance of Alzheimer’s disease ( Ramos-Cejudo et al, 2018 ). In studies of Alzheimer’s disease models, transplanted MSCs were found to promote the conversion of microglia from the CD86 + to the Arg-1 + state through paracrine effects ( Campos et al, 2022 ; Zhang R. et al, 2022 ). MSCs regulate microglial states by secreting the paracrine factors Galectin-1 (Gal-1) ( Seo et al, 2022 ), tumor necrosis factor-alpha-induced gene/protein 6 (TSG-6) ( Liu et al, 2019 ; Nam et al, 2020 ), and IL-13 ( Taj et al, 2018 ), etc.…”
Section: Mscs Regulate Microglial States Through a Paracrine Mechanis...mentioning
confidence: 99%
“…It has been suggested that the prolonged presence of microglial reaction after TBI increases the chance of Alzheimer’s disease ( Ramos-Cejudo et al, 2018 ). In studies of Alzheimer’s disease models, transplanted MSCs were found to promote the conversion of microglia from the CD86 + to the Arg-1 + state through paracrine effects ( Campos et al, 2022 ; Zhang R. et al, 2022 ). MSCs regulate microglial states by secreting the paracrine factors Galectin-1 (Gal-1) ( Seo et al, 2022 ), tumor necrosis factor-alpha-induced gene/protein 6 (TSG-6) ( Liu et al, 2019 ; Nam et al, 2020 ), and IL-13 ( Taj et al, 2018 ), etc.…”
Section: Mscs Regulate Microglial States Through a Paracrine Mechanis...mentioning
confidence: 99%
“…The main pathological features associated with AD are extracellular amyloid-β plaques (Aβ), hyperphosphorylation of tau protein, neurofibrillary tangles (NFTs), neuron death, and synaptic loss in the hippocampus, cortex, and amygdala [4,5]. Aβ plays a critical pathogenic role in AD, all types of AD are characterized by the accumulation of Aβ, which triggers a series of neuroinflammations, culminating in neuronal dysfunction and death [6].…”
Section: Introductionmentioning
confidence: 99%